Concurrent chemoradiation in head and neck cancers with weekly cisplatin: analysing toxicities - Vias, Poorva; Gupta, Manoj; Seam, Rajeev Kumar; Gupta, Manish; Fotedar, Vikas; Ahuja, Rachit (International Journal of Research in Medical Sciences, 2019)
Background: Head and neck cancers constitute 6% of cancers worldwide. The management requires a multidisciplinary approach. Concomitant chemoradiotherapy with cisplatin is the standard approach for locally advanced head and neck cancers. The most commonly used regime uses three weekly cisplatin which is more toxic. Low-dose once-a-week cisplatin is substituted because of perceived lower toxicity and convenience. Methods: Squamous cell carcinoma of stage III, IVA and IVB of oropharynx, hypopharynx and larynx were studied for one year. 82 patients were studied. Total dose of radiation was 66Gy/33#/6 ½ weeks from Monday to Friday with inj. Cisplatin 40mg/m2 i.v. infusion weekly. Results: 88% of patients were able to complete five or more weekly chemotherapy cycles with cumulative dose of 200mg/m2. Grade 2 and 3 acute toxicities were seen in weekly cisplatin arm but were conservatively managed. Conclusions: Weekly cisplatin can be used with concurrent radiotherapy as the acute toxicities are manageable and is well tolerated.